Optimisation of electrodeposition parameters on the mechanical properties of nickel cobalt coated mild steel - Yusoff, N.H.N. (Science and Technology Research Institute for Defence, 2018)
This paper discusses the effect of electrodeposition parameters of deposited nickel (Ni) cobalt (Co) from alkaline bath on commercial marine-grade mild steels. Prior to the deposition process, the Ni- Co samples were subjected to a two-level factorial design of experiment (DoE) to optimise the electrodeposition parameters, namely current density, electrolyte temperature and stirring speed. These electrodeposition parameters potentially affect the following responses of the coatings: microhardness, current efficiency and Co content. Current density contributes major outcome on the coating properties. Microhardness, current efficiency and Co content were significantly influenced by the current density. However, by changing the electrolyte temperature, a significant effect on current efficiency was noted. In conclusion, Ni-Co coated steels, with the highest current density of 50 mA/cm2 and the highest electrolyte temperature of 50 Â°C, were most preferred. Â© Science & Technology Research Institute for Defence (STRIDE), 2018.